2005
DOI: 10.1212/01.wnl.0000167130.31618.0a
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset ALS with long-term survival associated with spastin gene mutation

Abstract: The authors report a 73-year-old patient with a natural history of early-onset ALS for 49 years presenting with limb and bulbar amyotrophy and a pyramidal syndrome. Analysis of the locus SPG4 identified a heterozygous duplication mutation (c.304_309dupGCCTCG) within exon 1 of the spastin gene. We propose that sequence alterations of spastin may comprise a genetic risk factor in a greater spectrum of motor neuron disorders including clinical variants of ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 11 publications
1
28
1
Order By: Relevance
“…However, in our case series we found only two familial cases [11]. In a recent case report a specific clinical ALS subtype characterized by P_UMN, early-onset ALS, and long-term survival was associated with the spastin gene [17]. On the other hand, Turner et al [4] observed that older age at onset in a clinicalbased setting did not exclude long survival.…”
Section: Discussioncontrasting
confidence: 52%
“…However, in our case series we found only two familial cases [11]. In a recent case report a specific clinical ALS subtype characterized by P_UMN, early-onset ALS, and long-term survival was associated with the spastin gene [17]. On the other hand, Turner et al [4] observed that older age at onset in a clinicalbased setting did not exclude long survival.…”
Section: Discussioncontrasting
confidence: 52%
“…(dupA102,S103) (19) are located in this N-terminal region of spastin. None of these changes in spastin prevented atlastin recruitment in the cotransfection assay (Table 1, which is published as supporting information on the PNAS web site).…”
Section: Resultsmentioning
confidence: 99%
“…These include a case of rapidly progressive spinal and bulbar upper motor neuron syndrome [9] and that of a patient with early onset ALS and long term survival [10]. Also, in a large screen of HSP patients, neurophysiologic evidence of lower motor dysfunction was recorded in a subgroup of individuals harboring mutations in SPG4, one of whom showed progressive bulbar dysfunction and respiratory insufficiency [11].…”
Section: Discussionmentioning
confidence: 99%